Elderly‐onset degenerative "lumbar spondylotic myelopathy" in a patient with a low‐placed spinal cord successfully treated by laminotomy: a case report. Issue 12 (5th November 2015) - Hashimoto, Ko; Tsubakino, Takumi; Hoshikawa, Takeshi; Nakagawa, Tomowaki; Inawashiro, Takashi; Kokubun, Shoichi; Itoi, Eiji; Tanaka, Yasuhisa
Key Clinical Message: The authors report a rare case of elderly‐onset "lumbar spondylotic myelopathy" occurred on a low‐placed spinal cord compressed at multiple levels with thickened ligamenta flava. A posterior decompression surgery could alleviate neurological symptoms successfully instead of untethering of the spinal cord, a widely accepted surgery for tethered cord. Abstract : The authors report a rare case of elderly‐onset "lumbar spondylotic myelopathy" occurred on a low‐placed spinal cord compressed at multiple levels with thickened ligamenta flava. A posterior decompression surgery could alleviate neurological symptoms successfully instead of untethering of the spinal cord, a widely accepted surgery for tethered cord.